Wot Analysis Of The Environmental Agency Of Bengkulu City In Waste Management In Bengkulu City - Oktanindya, Fadillah; Lorita , Evi; Imanda , Antonio (CV. Utami, 2025)
This study aims to analyze the strengths, weaknesses, opportunities, and threats (SWOT) in waste management conducted by the Environmental Agency (DLH) of Bengkulu City. The research employed a descriptive qualitative method with data collection techniques including interviews, observations, and documentation. The findings reveal that DLH’s strengths lie in clear regulations, strong support from the local government, and innovative programs such as waste banks and community clean-up activities. However, weaknesses include limited funding, low public awareness, and insufficient use of technology. Opportunities are seen in community participation and collaboration with the private sector, while threats involve the continuously increasing volume of waste and the lack of modern processing facilities. The SWOT analysis indicates that strategies should focus on maximizing community collaboration supported by existing regulations, enhancing environmental education and outreach, and strengthening waste management infrastructure to achieve more effective and sustainable practices.